The Effect of Accrual-GAS on the Financial Reporting Reliability With HR Capacity as Mediating Variables (Jurnal Dinamika Akuntansi, 2017)
This research aimed to gets empirical evidence of the influence of human resource capacity with relation accrual-based government accounting standards on the reliability of financial reporting. This Research is a population research with the number of respondents 52 State Civil Apparatus who officiate as treasurer in each SKPD and employees in the accounting field in BPPKAD Kudus. Analysis method for hypothesis in this research used path analysis. The results of this research indicate that accrual basis government accounting standards and the capacity of human resources has a positive influence to the reliability of financial reporting, while accrual based government accounting standards have a positive effect on the capacity of human resource, but the capacity of human resources is not mediate the influence between accrual based government accounting standards to reliability of financial reporting. Conclusion of this study says that implementation of accrual based in Kudus District can support reliability of financial reporting and the capacity of State Civil Apparatus who officiate as treasurer in each SKPD and employees in the accounting field in BPPKAD Kudus also supports the created of financial reporting reliability.